Effects of Side Load Chains of a Combine Harvester on Unbalanced Dynamic Vibrations of Its Threshing Drum - Yu Zhiwu; Li Yaoming; Wang Xinzhong; Tang Zhong; Jiahui Lu (International Journal of Rotating Machinery)
In order to study the influence of the side drive on the balance state of the threshing drum, this paper used the side eccentric load chain drive as the power on the threshing drum dynamic balance test bench. By analyzing the influence of different radial phases, different axial distances, and spiral combinations of the threshing drum on the counterweight, this paper studies the law of the effect of side partial load chain drive on the dynamic balance of the threshing drum and finds that the side chain drive has obvious influence on the unbalance phase of the threshing drum and the change of the axial distance of unbalance has little effect on the equilibrium state of the threshing drum. And from this, a vibration balance method based on the equivalent unbalance of the chain drive is proposed, which can predict and calculate the unbalance of the threshing drum. The unbalance of the threshing drum predicted by this method is smaller than the actual measured unbalance. The maximum error is 32.64% and the minimum error is 4.6%. In the two tests, the predicted unbalance is 1.24 mm/s in amplitude and 270 degrees in phase and amplitude 1.4 mm/s and phase 120 degrees, respectively. The measured unbalance is amplitude 1.587 mm/s and phases 286 degrees. The error between prediction and actual measurement is less than 32.64%, and the unbalance amplitudes that can be reduced by one-time dynamic balance are 0.856 mm/s and 0.674 mm/s, respectively. The research results in this paper provide an effective method for the balance state of the multidrum side chain transmission.